Cardiac practice during the second year of COVID-19 pandemic: are we going back to normal?. (11th May 2022) - Dakhil, Z A; Cader, F A; Oz, TUG˘BA; Borreli, NUNZIA
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Little data is known regarding the impact of the COVID-19 pandemic on cardiac services during the second year. This globally distributed survey aimed to study the impact of the pandemic on cardiovascular services, type of PPE currently used by participants and their academic achievements during pandemic. Methods: A 23-item online survey was distributed via social media among HCPs involved in cardiac services. Survey items assessed the proportion of change in various cardiac services in 2021, as compared with 2020. Results: Among 111 respondents, 54.95% were resident in Asia, while 27.02% were resident in Europe, see Figure (1). Among total respondents; 57.7 % were females. 58.6% of respondents were from COVID-19 designated hospitals. Interventional cardiologists constitute 46.8% of respondents, clinical cardiologists were 22.5%, 12.6% were specialising in cardiac imaging, while 9% were electrophysiologists. 55% were consultants/attendings while 34.2% were fellows/ trainees. Proportions of return of cardiac services to pre-pandemic states are depicted in Figure (2). The highest return to pre-pandemic services were in emergency coronary catheterisation (25.2%), 21.6% of respondents noted return to pre-pandemic states in elective coronary catheterizations, and trans-thoracic echocardiograms [TTE]. Telemedicine was used by 64.9% of outpatient consultations. 94.6% of respondents were vaccinated. Respondents reported that most used PPE during their daily practice was surgical mask (69.36 %) followed by N95/FFP mask (53.15%). 30.6% reported decline in conference participation as faculty/speaker, while 21.6% reported decline in publications during the pandemic. Conclusion: In an increasingly vaccinated global cardiology workforce, cardiac services are gradually picking up to pre-pandemic rates, with the highest being noted for coronary catheterisations and trans-thoracic echocardiograms.